AN SNP MARKER POTENTIALLY LINKED TO SOMATIC EMBRYOGENESIS OF OIL PALM (Elaeis guineensis) - Irang Wahyunanto; Diana E Waturangi; Nurita Toruan-Mathius; Adi Yulandi (SEAMEO BIOTROP, 2017)
Oil palm (Elaeis guineensis) is one of the most important oil-bearing crops in the world. This crop can be vegetatively propagated only using tissue culture technique. Oil palm tissue culture technique has low efficiency, with callogenesis and embryogenesis stages as the limiting factors. Genetic factor has a major role in determining the success rate of these two stages. The use of molecular markers which represent the rate of embryogenesis or callogenesis has the potential to improve the efficiency of oil palm tissue culture process. In this study, SNP mining was conducted on embryogenesis transcriptome data, oil palm cDNA database, oil palm genome database, and oil palm SNP marker database in NCBI. The objective of this study was to obtain SNP marker which represents the embryogenesis potential, to be further used in marker-assisted selection of oil palm ortets. One SNP (EMB6) showed significant association with embryogenesis rate. This SNP was found in one of Auxin Response Factor (ARF) family genes. The nucleotide replacement from adenine to guanine changed the 307ⁿᵈ amino acid from isoleucine to methionine. Oil palms with adenine homozygote (A/A) pattern on EMB6 showed an 8-fold higher chance to produce significantly higher embryogenesis rate than adenine–guanine heterozygote (A/G).